Developing Language Teacher Autonomy through Action Research - Dikilitaş, Kenan; Griffiths, Carol (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book advances the theory of action research, analyzing how it can be used to develop autonomy among language teachers. Although acknowledging that the research process is not always linear, the authors proceed according to a clear progression which teachers can adapt to their needs. They provide examples, narratives, questions and tasks, and give multiple ideas for establishing research questions, choosing appropriate methodologies, adapting to existing contexts, and collecting data. They also suggest possible instruments, and give clear instructions for carrying out the most common kinds of statistical procedures, and ideas for presenting, discussing, and writing up research findings. In spite of its practical bias, the book is theoretically and ethically rigorous, and contains an extensive glossary for quick and easy reference. It will appeal to trainee teachers, in-service teachers wanting to expand their own professional horizons or working for a higher qualification, and is an invaluable reference for teacher-educators and scholars.